Tuning of catalytic activity by thermoelectric materials for carbon dioxide hydrogenation - Achour, Abdenour; Chen, Kan; Reece, Michael J.; Huang, Zhaorong (Wiley, 2017)
An innovative use of a thermoelectric material (BiCuSeO) as a support and promoter of catalysis for CO2 hydrogenation is reported here. It is proposed that the capability of thermoelectric materials to shift the Fermi level and work function of a catalyst lead to an exponential increase of catalytic activity for catalyst particles deposited on its surface. Experimental results show that the CO2 conversion and CO selectivity are increased significantly by a thermoelectric Seebeck voltage. This suggests that the thermoelectric effect can not only increase the reaction rate but also change chemical equilibrium, which leads to the change of thermodynamic equilibrium for the conversion of CO2 in its hydrogenation reactions. It is also shown that this thermoelectric promotion of catalysis enables BiCuSeO oxide itself to have a high catalytic activity for CO2 hydrogenation. The generic nature of the mechanism suggests the possibility that many catalytic chemical reactions can be tuned in situ to achieve much higher reaction rates, or at lower temperatures, or have better desired selectivity through changing the backside temperature of the thermoelectric support.
Keywords: Carbon dioxide hydrogenation; Electrochemical energy; Promotion of catalysis; Thermoelectric materials; Work function